1990
DOI: 10.1093/ptj/70.6.340
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Walking Pattern Changes in the Fit and Healthy Elderly

Abstract: A descriptive study of the biomechanical variables of the walking patterns of the fit and healthy elderly compared with those of young adults revealed several significant differences. The walking patterns of 15 elderly subjects, selected for their active life style and screened for any gait- or balance-related pathological conditions, were analyzed. Kinematic and kinetic data for a minimum of 10 repeat walking trials were collected using a video digitizing system and a force platform. Basic kinematic analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
535
9
36

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 864 publications
(630 citation statements)
references
References 12 publications
50
535
9
36
Order By: Relevance
“…On die contrary, the heightened arousal demonstrated by OA could be harmful to their safety. This arousal may increase cocontraction and joint stiffness, which may cause difficulty during trip recover}' (Winter et al, 1990), specifically under time constrained conditions. As well, increased arousal may demand the allocation of more attention to postural control making individuals unable to detect sudden environmental risks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On die contrary, the heightened arousal demonstrated by OA could be harmful to their safety. This arousal may increase cocontraction and joint stiffness, which may cause difficulty during trip recover}' (Winter et al, 1990), specifically under time constrained conditions. As well, increased arousal may demand the allocation of more attention to postural control making individuals unable to detect sudden environmental risks.…”
Section: Resultsmentioning
confidence: 99%
“…These conservative movements may cause, co-contraction, leading to joint stiffness and difficulty 7 during trip recovery (Winter, et al, 1990). However, findings from previous work (Adkin et al, 2002;Carpenter et al, 2001;Adkin et al, 2000;Carpenter et al, 1999) have revealed that YA adopt a stiffening strategy under conditions of postural threat which may be beneficial to postural control.…”
Section: Implications For Fear Of Fallingmentioning
confidence: 97%
See 1 more Smart Citation
“…Gait adaptation frequently occurs as a result of aging. Elderly people often walk with shorter step length with a wider base of support, and slower transitional acceleration of the whole body center-of-mass (COM) [13,24]. Additionally, higher heel contact velocities have been reported for the frail elderly population at the time of the heel contact phase of the gait cycle [13].…”
Section: Introductionmentioning
confidence: 99%
“…Elderly people often walk with shorter step length with a wider base of support, and slower transitional acceleration of the whole body center-of-mass (COM) [13,24]. Additionally, higher heel contact velocities have been reported for the frail elderly population at the time of the heel contact phase of the gait cycle [13]. These gait adaptations further increase risk of slipping, for example, higher heel contact velocity can increase horizontal ground reaction force in relation to vertical ground reaction force and as a result, friction demand can increase [25].…”
Section: Introductionmentioning
confidence: 99%